Cost Reduction Strategy In Manufacturing Industries Empirical Evidence From Indonesia - Fadjarenie, Rien Agustin; Rachmadani, Citra; Tarmidi, Deden (Jurnal Akuntansi, 2024)
The COVID-19 pandemic has forced manufacturing industries to be efficient in multiple fields. This study examines the effect of raw material management using Material Flow Cost Accounting and waste cost for Non-Product Output cost on implementing cost reduction strategies. Data was gathered by analyzing annual financial reports as well as sustainability reports. The study finds that organizations can reach efficiency by managing the cost of the raw materials using Material Flow Cost Accounting and Non-Product Output costs when implementing a cost reduction strategy. The research contributes to developing the concept of cost reduction through the Environmental Management Accounting approach, which is still rare in this field, in addition to the traditional method of cost accounting that organizations have carried out to achieve cost efficiency.